Blockchain can be the best technology for reducing cyber risks in financial services industry - Soma HariPrasad (Journal of Management and Science, 2019)
Blockchain is a decentralized ledger where each member has access to the latest copy of encrypted ledger which consist of deals and transactions taken place with the help of digital currencies for validating. Basically ,it's a distributed database that is tamper proof which holds batches of individual transactions. Each completed block has different features like Chronology, linearity, time stamp and information links to the previous blocks.The present research identifies different cyber security applications that are used by architects viz.,cryptography,Personal Identification Information, and web applications in implantationof block chain technology with the help of peerreview literature in managing the cyber risks anddrive the future of financial services industry by using IOT,Machine Learning andArtificial Intelligence etc.,